Grade 3 endometrioid adenocarinoma of the lower uterine segment diagnosed 6 weeks after a term delivery: A case report and literature review - Zoe Laing-Aiken; Sara Ooi; Gaithri Mylvaganam; Huan Xie; Joanne Ludlow; Selvan Pather (Elsevier, 2021)
Background: Endometrial cancer is the most common gynaecological malignancy in Australian women. Less than 5% of cases occur in women under 40 years of age and it is rarely associated with pregnancy. Most cases associated with pregnancy are diagnosed after first trimester loss. Only 14 cases of endometrial cancer diagnosed post-partum are reported in the literature. These cases were diagnosed up to 15 months post-partum. The histopathological classification was low grade in 12 patients and high grade in two patients. Case: We describe a 37 year old woman, who presented after her second vaginal delivery (at 37 weeks of gestation) with suspected retained products of conception (RPOC). She had a dilation and curettage leading to the diagnosis of endometrial cancer six weeks post-partum. She underwent a total laparoscopic hysterectomy, bilateral salpingo-oophorectomy and bilateral sentinel node biopsy. Histopathology confirmed a stage 1B grade 3 endometrioid adenocarcinoma located in the lower uterine segment with widespread lymph-vascular invasion and no other evidence of malignancy. She is planned to complete six cycles of adjuvant carboplatin/ paclitaxel chemotherapy, followed by pelvic external beam radiotherapy. Discussion: We report the second case of a high-grade endometrial cancer diagnosed post-partum. The bulk of this tumour was in the lower segment of the uterus, which together with the fundal placenta, likely permitted the pregnancy progressing to term. Endometrial cancer should be considered a rare cause of abnormal post-partum bleeding. Curettage and histopathology examination is recommended in cases that do not resolve with conservative measures to exclude this rare complication.